Upaya Meningkatkan Konsentrasi Belajar Siswa KMS (Kartu Menuju Sejahtera) Menggunakan Konseling Kelompok Bagi Siswa - Ikawati, Mei Prihantini Diyah (Universitas Ahmad Dahlan, 2015)
This research aims to know the effectiveness of group counseling service to improve the learning concentration of the students holding Road to Prosperity Cards (KMS-Kartu Menuju Sejahtera). The research employed action research in the implementation. The subject of the research is five students from grade VIII of SMP Negeri 15 Yogyakarta which were selected using purposive sampling technique. The data were collected using the quessionaire on learning concentration and observation guidelines. To examine the effectiveness of group counseling service, the data is analyzed using t-test formula. The data analysis results show the t-value of 9.215 > t table (2.2776). The average score of the pretest on learning concentration was 145.4. The score improved at the post test on learning concentration, showing the average score of 167.4. Based on the research results, it can be concluded that group counseling service is effective to improve the learning concentration of the students holding Road to Prosperity Card. This research can be used by the teachers of guidance and counseling to help the students to improve their learning concentration through group counseling service.